0051 Altered Endogenous Circadian Rhythm of the Endocannabinoid Anandamide by Body Mass Index. (12th April 2019) - Bowles, Nicole P; Thosar, Saurabh S; Herzig, Maya X; Clemons, Noal A; Sauber, Garrett; Roberts, Sally A; Berman, Alec M; Morimoto, Miki; Stewart, Alicia V; McHill, Andrew W; Butler, Matthew P; Emens, Jonathan S; et al.
Abstract: Introduction: The endocannabinoid anandamide (AEA) signals ubiquitously throughout the body and has been shown to modulate endocrine systems and sleep/wake cycles. Previous analyses suggest a diurnal variation in plasma levels of AEA. We sought to determine the endogenous circadian profile of AEA and how this distribution may vary by body mass index (BMI) and sleep. Methods: Thirteen healthy participants (mean age, 51 years; 9 females; 8 lean mean BMI, 24.5 kg/m 2 ; 5 non-lean mean BMI, 36.7 kg/m 2 ) underwent a laboratory protocol that balanced eucaloric meals and sleep opportunities evenly across the circadian cycle (achieved by scheduling 10 identical, recurrent 5 h 20 min 'days' in dim light thereby desynchronizing the circadian and behavioral cycles). Blood was sampled before sleep and upon awakening through a midline catheter. AEA was quantified by liquid chromatography-mass spectrometry. Salivary melatonin was used to assess circadian phase (phase marker = dim-light melatonin onset [DLMO]). Results: Average plasma AEA was lower in lean compared to non-lean participants (means: 0.4 pmol/mL versus 0.8 pmol/mL, respectively; p=0.024). The endogenous rhythm of plasma AEA was driven by non-lean participants: peak to trough range 0.65-0.96 pmol/mL; peaking in the biological afternoon ( 2:45pm, 18 hours after DLMO; p=0.01) with no significant rhythm in lean participants. Finally, the circadian rhythm of AEA did not significantly differ when measured immediately before or after sleep. Conclusion: The variation in AEA across 24 hours is modulated by the circadian system in non-lean individuals, whereas levels remain relatively constant in lean healthy adults. Future studies are needed to determine if the 1.5-fold increase of peak to trough in AEA in non-lean adults is related to an increase in hunger cues and caloric intake that may account for increased BMI. This initial analysis does not account for sleep efficiency, which may alter AEA levels across sleep. Support (If Any): Ford Foundation, R01 HL125893, NCC 9-58, F32HL131308, and UL1TR000128.